Efektivitas Penerimaan Retribusi Parkir Dalam Upaya Meningkatkan Retribusi Daerah Pada Bapenda Kabupaten Bekasi 2018-2020 - Dewin Chintia Putri; Rahadi Pratomo (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Parking levies are services for special parking spaces provided, owned, and/or managed by the Regional Government. The phenomenon in this study is that there is still a lack of public awareness of parking retribution payments, resulting in the realization of parking retribution revenue targets not being achieved. The purpose of this study was to analyse the effectiveness of parking retribution receipts to increase regional levies at the Bekasi Regency Bapenda in 2018-2020, as well as obstacles and efforts related to parking retribution receipts. This study uses a descriptive qualitative approach. The theory used in this study is the theory of effectiveness from Steers with three indicators, namely optimization of goals, system design, and human behavior. The results of this study show the effectiveness of parking retribution receipts to increase regional retribution in Bekasi Regency in 2018-2020 in terms of the effectiveness of parking retribution receipts in Bekasi Regency, which has been running effectively, where the average percentage of parking retribution receipts reaches 93.59%, and with the average percentage of the contribution of parking fees to the Bekasi Regency regional retribution in 2018-2020 reaching 0.88%.